2012
DOI: 10.1002/pola.26405
|View full text |Cite
|
Sign up to set email alerts
|

The design, synthesis, and nonlinear optical properties of novel X‐type polyurethane containing dicyanovinylnitroresorcinoxy group with enhanced SHG thermal stability

Abstract: Novel X‐type polyurethane 5 containing 4‐(2′,2′‐dicyanovinyl)‐6‐nitroresorcinoxy groups as nonlinear optical (NLO) chromophores, which constitute parts of the polymer backbone, was prepared and characterized. Polyurethane 5 is soluble in common organic solvents such as acetone and N,N‐dimethylformamide. It shows thermal stability up to 280 °C from thermogravimetric analysis with a glass transition temperature (Tg) obtained from differential scanning calorimetry thermogram of around 120 °C. The second harmonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Before poling, the films appeared very flat and clean. After poling, however, the films were changed, and numerous hills and valleys appeared on the poled films, which could be seemed as the evidence of the chromophores alignment during the poling process . The AFM images further indicate that the synthesized EO polycarbonates have excellent film‐forming properties, it also demonstrated that the materials have excellent dielectric strength because good film quality was retained after high electric field poling according to the AFM scans of the poled films.…”
Section: Resultsmentioning
confidence: 88%
“…Before poling, the films appeared very flat and clean. After poling, however, the films were changed, and numerous hills and valleys appeared on the poled films, which could be seemed as the evidence of the chromophores alignment during the poling process . The AFM images further indicate that the synthesized EO polycarbonates have excellent film‐forming properties, it also demonstrated that the materials have excellent dielectric strength because good film quality was retained after high electric field poling according to the AFM scans of the poled films.…”
Section: Resultsmentioning
confidence: 88%
“…Nonlinear optical materials have been attracting considerable attention due to their potential applications in the field of electro-optic devices including ultrafast optical switches, high-speed optical modulators, and high-density optical data storage media [1][2][3][4][5][6][7][8][9][10][11][12]. It is well known that organic and inorganic materials with high dipolar electronic systems exhibit large NLO effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical (NLO) materials have drawn much attention in the past two decades because of their potential applications in the field of electro‐optic technology such as optical data transmission, optical data storage and optical information processing . Compared with traditional inorganic materials, organic NLO polymers have many advantages such as higher nonlinear optical activity, faster response time, low cost, wide response waveband, high optical damage threshold and good processability for forming electro‐optic devices.…”
Section: Introductionmentioning
confidence: 99%